2022
DOI: 10.1038/s41598-022-13566-7
|View full text |Cite
|
Sign up to set email alerts
|

Audience effect on domestic dogs’ behavioural displays and facial expressions

Abstract: In the present study we investigated the influence of positive and negative arousal situations and the presence of an audience on dogs’ behavioural displays and facial expressions. We exposed dogs to positive anticipation, non-social frustration and social frustration evoking test sessions and measured pre and post-test salivary cortisol concentrations. Cortisol concentration did not increase during the tests and there was no difference in pre or post-test concentrations in the different test conditions, exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 72 publications
1
21
2
Order By: Relevance
“…Displacement behaviours of “blinking”, “nose licking” and “lip wiping” were positively associated with a “non-reactive” attitude both in the threatening and in the neutral condition. A recent study from our group found that these patterns are exhibited with higher probability in a frustration evoking situation (denial of food reward) when a human partner was visible compared to when it was not visible, suggesting a possible communicative valence of these visual signals (Pedretti et al 2022 ). Furthermore, a previous study by Firnkes and colleagues found that lips licking is displayed more frequently in the mild threatening/friendly approach compared to a threatening screaming and physical threat approach (Firnkes et al 2017 ) and it was frequently associated with active submissive behaviours (ears flattened, tail wagging, crouched posture), suggesting a potential function in mediating social encounters.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Displacement behaviours of “blinking”, “nose licking” and “lip wiping” were positively associated with a “non-reactive” attitude both in the threatening and in the neutral condition. A recent study from our group found that these patterns are exhibited with higher probability in a frustration evoking situation (denial of food reward) when a human partner was visible compared to when it was not visible, suggesting a possible communicative valence of these visual signals (Pedretti et al 2022 ). Furthermore, a previous study by Firnkes and colleagues found that lips licking is displayed more frequently in the mild threatening/friendly approach compared to a threatening screaming and physical threat approach (Firnkes et al 2017 ) and it was frequently associated with active submissive behaviours (ears flattened, tail wagging, crouched posture), suggesting a potential function in mediating social encounters.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, a previous study by Firnkes and colleagues found that lips licking is displayed more frequently in the mild threatening/friendly approach compared to a threatening screaming and physical threat approach (Firnkes et al 2017 ) and it was frequently associated with active submissive behaviours (ears flattened, tail wagging, crouched posture), suggesting a potential function in mediating social encounters. Considering results of both studies these signals are meaningful in a social context (Pedretti et al 2022 ); however, their function is not limited to a potential conflict situation (Firnkes et al 2017 ). The appeasement function is thus not fully confirmed: although these behaviours were exhibited predominantly by dogs that lacked offensive/defensive motivation (“non-reactive” dogs), there was not a higher frequency of such behaviours in the more conflictual vs. neutral context as expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in Phase 4, they wagged their tail more compared to the other phases. A recent study showed how tail wagging is associated with the presence of a human audience, and not linked with measures of arousal, suggesting a possible communicative intent in the expression of this behavior (Pedretti et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of an audience in an emotional context is an important element to be considered when investigating facial expressions (of emotions) in dogs, as shown by a recent study of Pedretti et al 24 . Similarly to 19 , 22 , the authors also exposed dogs to positive anticipation, and non-social and non-social frustration, evoking test sessions.…”
Section: Introductionmentioning
confidence: 99%